Who Is Benefiting from Airbnb? Assessing the Redistributive Power of Peer-to-Peer Short-Term Rentals. Issue 3 (3rd July 2021) - Mermet, Anne-Cécile
Abstract : This article aims to bring empirical evidence to the debate on the redistributive effects of the sharing economy, using Airbnb as an example. Peer-to-peer short-term rental platforms provide every inhabitant of a tourism area with the opportunity to be a stakeholder of the local accommodation industry by leasing an underutilized part of their property to tourists. Therefore, Airbnb could be seen as a way to redistribute the income influx brought by tourism to a whole community, beyond the professionals of the hotel industry. Yet, very little is known about the categories of the population who are actually engaged in this business. Based on data on hosts advertising listings in the Reykjavík Capital Region (Iceland), this article shows that affluent households are the most represented among the Airbnb hosts. It demonstrates that the most profitable listings are advertised by upper class households, whereas low-income households are significantly underrepresented among hosts and have less profitable listings. This article therefore confirms that Airbnb does not benefit homogeneously across all categories of the population and that it reproduces inequality patterns in tourism cities.